2020
DOI: 10.3390/pharmaceutics12090900
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Mycobacterium bovis BCG Fermentation and Storage Survival

Abstract: Mycobacterium bovis Bacillus Calmette–Guérin (M. bovis BCG) was generated over a century ago for protection against Mycobacterium tuberculosis (Mtb) and is one the oldest vaccines still in use. The BCG vaccine is currently produced using a pellicle growth method, which is a complex and lengthy process that has been challenging to standardise. Fermentation for BCG vaccine production would reduce the complexity associated with pellicle growth and increase batch to batch reproducibility. This more standardised gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The THP-1 cell line is an alternative study model that serves as a support to understand various cellular responses without assuming that the results are the same as those of macrophages obtained live from patients [20]. The spectrophotometric absorbance values observed for each strain over time, which were used to estimate the log phase for maximal growth, were similar to those reported by other authors examining different BCG strains [29,30]. The differential amount of intracellular bacteria we found over time could be associated with the phenotypic characteristics of each strain and could explain both the phagocytosis process and the immune response [23][24][25]31].…”
Section: Discussionsupporting
confidence: 61%
“…The THP-1 cell line is an alternative study model that serves as a support to understand various cellular responses without assuming that the results are the same as those of macrophages obtained live from patients [20]. The spectrophotometric absorbance values observed for each strain over time, which were used to estimate the log phase for maximal growth, were similar to those reported by other authors examining different BCG strains [29,30]. The differential amount of intracellular bacteria we found over time could be associated with the phenotypic characteristics of each strain and could explain both the phagocytosis process and the immune response [23][24][25]31].…”
Section: Discussionsupporting
confidence: 61%
“…Among potential explanations for these variations, manufacturing processes that are difficult to standardize have been suggested. There, production using fermentation and defined chemical media have been shown to affect viability [15]. What other consequences that a change in the method of manufacturing BCG would have in terms of efficacy of protection remain to be determined.…”
Section: Benefits and Drawbacks Of Current Bcgmentioning
confidence: 99%
“…Solid mediums containing eggs, such as LJ and Ogawa, are the least expensive within these mediums yet can provide reliable results. It has been demonstrated that production through fermentation and specific chemical medium affects viability (2). Consequently, data regarding the influence of culture medium on the growth of Mycobacterium bovis (M. bovis) is still required for optimum quality control of BCG vaccines.…”
Section: Introductionmentioning
confidence: 99%